Information Value of Calculated Hematological Indices in the Assessment of Cardiac Risk in Oncological Surgery - D. A. Sokolov; I. A. Kozlov (Вестник анестезиологии и реаниматологии)
The objective: to study information value of the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in the cardiac risk assessment in abdominal oncological surgery.Subjects and Methods. 94 patients of 68 [62‒73] years old who underwent elective surgery were examined.Results. Cardiovascular comortbidity was diagnosed in 69 (73.4%) patients. 11 (11.7%) perioperative cardiovascular complications were registered. Cardiac mortality was 4.3%. Hematological indices were not associated with cardiovascular diseases (NLR: OR = 0.59‒1.42; 95% CI 0.14‒2.60; p = 0.29‒0.74, PLR: OR = 0.99‒1.00; 95% CI 0.97‒1.01; p = 0.31‒0.99). NLR and PLR were not predictors of cardiovascular complications (OR = 0.67; 95% CI 0.19‒2.37; p = 0.46 and OR = 1.00; 95% CI 0.99‒1.01; p = 0.68) and cardiac death (OR = 0.21; 95% CI 0.01‒8.05; p = 0.23 and OR = 0.99; 95% CI 0.98‒1.01; p = 0.79).Conclusion. NLR and PLR cannot be recommended for the cardiac risk assessment in abdominal oncological surgery.